Essential trace elements in meat, spleen and liver of Brahman Cross steers reared in intensive production system in Bandung, Indonesia - Lestiani, D. D.; Santoso, M.; Setyowati, E. Y.; Kurniawati, S.; Adventini, N.; Damastuti, E. (Diponegoro University, 2018)
In this study the determination of micro mineral elements (selenium, iron and zinc) in meat, spleen and liver of beef were carried out. Brahman cross steers reared under intensive production system in feedlot for 87 days. Samples of meat, spleen and liver were collected from 16 steers aged 24-36 months with four types of feeding treatment, feeding without Se (group I) and feeding with additional supplementary of 0.3 ppm selenium for 25, 50 and 75 days (group II, III and IV, respectively). Samples characterization were carried out by instrumental neutron activation analysis (INAA) using irradiation facility in G.A Siwabessy Serpong reactor. Analysis results showed that there is an increasing of selenium content in meat and liver after 75 days feeding. The mean of selenium in liver for group I, II, III and IV were 0.13, 0.17, 0.20 and 0.31 mg/kg wet weight, respectively, while for liver were 0.43, 0.53, 0.60 and 0.70 mg/kg wet weight, respectively. The mean concentrations for iron in meat, spleen and liver were 11.85, 139, and 38.94 mg/kg, respectively, for zinc were 27.90, 21.70 and 25.27 mg/kg, respectively. In this study, the meat and liver contribute more than 100% of recommended daily allowance (RDA) of Se for children and adults. Spleen have contribution of RDA of Fe 53 to 154%, while the RDA of Zn is contributed mostly from meat by 21 to 56%.